Evaluasi Nilai Ekologi dan Sosial Budaya Berbasis Presepsi Masyarakat dan Pengunjung di Taman Merdeka Kota Metro - Ratih Timur Pradopo; Sugeng P Harianto; Gunardi Djoko Winarno (Institut Agama Islam Nasional Laa Roiba Bogor, 2024)
This research aims to analyze the environmental conditions of urban forests so that we can find out visitors' perceptions of urban forests and can evaluate the condition of urban forests based on visitors' perceptions. The sample taken in this research used the Accidental Sampling method, namely the technique of determining the sample taken based on who met the researcher so it could be used as a sample. From the research results, it can be concluded that Metro City Merdeka Park has an important role in maintaining the balance of the urban environment and the quality of life of its citizens. It has 14 tree species with a tree density of 81.13 and an area of ​​around 8,545.29 m2. Metro City Merdeka Park also has an ecological function. (beauty/aesthetics of urban space), and socio-cultural (social interaction). Based on the perception of visitors to Taman Merdeka Metro City, the socio-cultural aspect has a score of 4, namely good, the educational aspect has a score of 4, namely good, the ecological aspect has a score of 4, namely good and The behavioral aspect also has a score of 4, namely good.